(untitled) - Moss, Larissa T. (Boston, MA., 2003)
Business Intelligence Roadmap is a visual guide to developing an effective business intelligence (BI) decision-support application. This book outlines a methodology that takes into account the complexity of developing applications in an integrated BI environment. The authors walk readers through every step of the process--from strategic planning to the selection of new technologies and the evaluation of application releases. The book also serves as a single-source guide to the best practices of BI projects.
Keywords: Business intelligence,Decision support systems,Tình báo kinh doanh,Hệ thống hỗ trợ ra quyết định